Debt Crises and the Development of International Capital Markets - Sy, Amadou (IMF Working Papers; Working Paper ;, 2004)
Crises on external sovereign debt are typically defined as defaults. Such a definition accurately captures debt-servicing difficulties in the 1980s, a period of numerous defaults on bank loans. However, defining defaults as debt crises is problematic for the 1990s, when sovereign bond markets emerged. In contrast to the 1980s, the 1990s are characterized by significant foreign debt-servicing difficulties but fewer sovereign defaults. In order to capture this evolution of debt markets, we define debt crises as events occurring when either a country defaults or its bond spreads are above a critical threshold. We find that our definition outperforms the default-based definition in capturing debt-servicing difficulties and, consequently, in fitting the post-1994 period. In particular, liquidity indicators are significant in explaining our definition of debt crises, while they do not play any role in explaining defaults after 1994.